Taboos in interpersonal interaction (іn the Ukrainian phraseology and idioms) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the problem of taboos in Ukrainians interpersonal interaction and communication. It also investigates some features of mental taboo traits represented in Ukrainian phraseology and idioms stock. In the focus of this article stands verbalizing the scope of vices and negative acts perceived by society as undesirable and unacceptable. Analyzed set expressions and idioms demonstrate the ways of normative behavior regulation, politeness, respect and tact аspiration.
Keywords: taboo; national character; idiom; communicative behavior